MICROMECHANICS MODELS OF PARTICULATE FILLED ELASTOMER AT FINITE STRAIN DEFORMATION - YANG Hui (Jixie qiangdu, 2016)
This paper deals with a micromechanics-based model which is proposed for the finite strain deformation of filled elastomers based on generalized Eshelby ’s tensor and Mori-Tanaka ’s method. The present formulation leads to a clear explanation of the constraint effect of rubber-like matrix on the inclusions. Comparisons with experiments and other micromechanics models are conducted. It is observed that an improvement in predictive capability for the composite with randomly dispersed particles was achieved by the present method. Based on the latest experiment of single molecular chain,a compact network model is fatherly developed to reflect the microstructure effect on the stress-strain relations of rubbery polymer and the resulting composites.